Análise da função dos músculos do quadril em portadores de síndrome da dor patelofemural - Silva, Robson Alves da (2009)
The Patellofemoral pain syndrome is defined as a fore or retro patellar pain and it has multifactorial etiology, where the bad patellar alignment is the most acceptable hypothesis. However proximal factors to the knee, as the debility of the muscles of the hip, have been demonstrated as a contributing factor to the appearing of that syndrome. Purpose: To evaluate if exists a relation between the hip muscles performance and the development of the SDPF. Methods: Thirty women took part in this study. They were divided in two groups; a control group (fifteen asymptomatic subjects) and an experimental group (fifteen subjects with the diagnosis of SDPF). The muscle performance was evaluated in an isokinetic dynamometer, where it was verified the peak torque (PT), PT to body weight, PT time and the agonist/antagonist relation. It was also analyzed the electromyographic activity of the middle gluteus. The data was analyzed by the not paired t test at a significance level of 5%. Results:. Didn t have significant difference to the PT of the abductor muscles (p = 0,46) and lateral rotators of the hip (p = 0,17) between groups. Also didn t have significant difference to the PT values by the body weight, to these muscle groups either (p = 0,10 e p = 0,11, respectively). Didn t have significant difference between the amplitude of the signal (p = 0,05) and the onset of medium gluteus (p = 0,25) between the groups. Conclusion: In the experimental conditions realized, the study didn t demonstrate a relation between performance the hip muscles behavior and the development of the SDPF